Adaptive PSO with optimised firefly algorithms for secure cluster‐based routing in wireless sensor networks. (1st October 2019) - Pavani, Movva; Trinatha Rao, Polipalli
Abstract : One of the important considerations in a sensor network is energy consumption. Cluster‐based routing protocols are often proposed to reduce energy consumption. However, clusters are vulnerable due to malicious nodes. Malicious nodes inject fake messages to cluster‐header, which increases communication overhead and energy consumption. Secure cluster‐based routing is one of the most required solutions to consume more energy during data transmission. In this study, the authors propose a secure cluster‐based routing protocol (SCBRP) that uses adaptive particle swarm optimisation (PSO) with optimised firefly algorithms during data transmission in a wireless sensor network. The objective of this study is to minimise energy consumption over an individual node to improve the whole network lifetime. The proposed SCBRP is based on the hexagonal sensor network architecture, and it is designed by three processes to include energy‐efficient clustering, secure routing, and security verification. The performance of the proposed SCBRP is evaluated using NS‐3, and it is estimated by different metrics such as encryption time, decryption time, energy consumption, packet drop rate, and network lifetime. The simulation results are compared with the previous approaches and finally, the authors' proposed SCBRP is proved that it obtained better performance than previous approaches.